Agriculture Research Center Di Lahan Pasir Pantai Baru Yogyakarta (Dengan Pendekatan Green Architecture) - Saputro, Tendi Eko, Nur Rahmawati S , ST, MT, Ronim Azizah , ST, MT (2015)
Soil resource is a natural resource that is vital for human survival because of land resources is an input needed for every form of human activity such as agriculture, industrial areas, residential areas, roads for transport, the regions or recreational areas maintained their natural condition for scientific purpose. The availability of agricultural land decreased with the transfer land use from agricultural to non-agricultural. The agricultural sector in Java faced with the problem of conversion of land for industrial or residential and the problem of markets for agricultural products, in view of the island of Java has become the market Good for imported products. Therefore, the challenge for agriculture in The island of Java is how to increase productivity as narrowing land, improving product competitiveness in line with the rapid flow of imports and the strong demands for the promotion of exports, building the image of agriculture and to improve the welfare of farmers. One of the alternatives that can be taken in an effort to land supply for agriculture that is by utilizing marginal land as beach sand land farming. Land sand beach is a second problematic area after acid soil, sandy beach where marginal land potential for harnessed into productive farming land mainly for cultivation horticultural crops. Given Indonesia is an archipelago of 60% total area is water, so that there is a willingness in Indonesia land very wide beach sand that can be used for one of the sector pertaniaan such alternative land. Rice, CABEI, Melon, Dragon Fruit, Garlic Red Cabbage. Land is the land of beach sand containing clay, dust, and nutrients are minimal. As a result, sandy soil easier flow of water, approximately 150 cm per hour. Conversely, the ability of sand soil to store water is very low, 1.6 to 3% of the total water available. The wind in the southern coastal region was very high, about 50 km per hour. Winds it easily uproot the roots and tear down the plant. Of this final project planning process has several problems, that is: 1. How to locate and determine the appropriate location for the center agricultural research sand beach right? 2. How to design a building that region accommodate activities agricultural research center and beach sand support facilities in Yogyakarta. 3. How does the application of the concept of Green Architecture in the design Agriculture Research Center in New Coastal Sand Land Yogyakarta Thus the authors had the initiative to create a place which will serve as a center of agricultural research (plant) in the land sand beach. Now where in it there is sand land planted with varioustype of plant cultivation, research centers, study centers of cultivated plants, libraries, laboratories, auditorium, gallery, training centers, educational tours, tower view, homestead expatriates / guests and so on. The venue is expected to add to the knowledge coastal communities on agricultural land sand beach in Indonesia. In addition it is often used as a focused educational tours the plants in the land of sand beaches and a training hall. So in essence is The place as a center of plant research in the field and a sand beach educational tours sand plant.